YOUTH’S SOCIAL PRACTICE IN YOUTH ORGANIZATION AND ITS CONTRIBUTION TO BORDER COMMUNITIES IN SEBATIK TIMUR, KALIMANTAN UTARA - Ridwan Tajul Fahmi; Mohammad Rousyan Fikri Qowim; Tri Gunawan; Nur Faridatul Janah; Nanda Harda Pratama Meiji (Jurnal Ilmu Sosial Mamangan, 2021)
This article aims to analyze the youth’s social practice in organization and its contribution to border communities in Sebatik Island, Indonesia-Malaysia Border. This research was conducted using descriptive qualitative approach. Data collection was carried out using interview, observation, and documentation methods. The result of research showed that social practice conducted by the youths in organization in Indonesia-Malaysia border is to establish organization based on shared hobby, background, and objective. Individual youths and organizations have different habitus and capital. Some youths have active habitus in many organizations and hold activities for internal members of organization and for the public. However, some others are active in internal organization only and focus on improving their self competency. Basic capital of organization is cultural capital of communication. Meanwhile, the supporting capital is social capital of intra- and inter-organization relation, symbolic capital in the form of public’s recognition that an individual has good organizational competency, and thereby is trusted to lead, and material economic capital.